2009
DOI: 10.1007/s10457-009-9236-8
|View full text |Cite
|
Sign up to set email alerts
|

Plant species richness and diversity in urban and peri-urban gardens of Niamey, Niger

Abstract: Urban and peri-urban agriculture (UPA) significantly contributes to food and nutritional security of urban dwellers in many African countries. Economic and demographic pressures often lead to transformation of subsistence-oriented traditional homegardens into commercial production units. Such transformation is claimed to result in decreasing plant diversity, particularly of local species. A study was therefore undertaken in 51 gardens of Niamey, Niger, to assess the factors determining plant diversity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
67
3
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 25 publications
13
67
3
10
Order By: Relevance
“…Being complying with the findings of Abdoellah et al (2006), Bernholt et al (2009) and Major et al (2005), this study too implies a negative relationship between the degree of commercialization and plant diversity, by reporting a negative coefficient for the IEI. When the objective becomes the commercialization, people tend to grow more plants in the same species as it facilitates more convenient management, than that of managing multiple plants in different species.…”
Section: Semsupporting
confidence: 82%
“…Being complying with the findings of Abdoellah et al (2006), Bernholt et al (2009) and Major et al (2005), this study too implies a negative relationship between the degree of commercialization and plant diversity, by reporting a negative coefficient for the IEI. When the objective becomes the commercialization, people tend to grow more plants in the same species as it facilitates more convenient management, than that of managing multiple plants in different species.…”
Section: Semsupporting
confidence: 82%
“…In Niger, higher diversities of species were present in large periurban gardens (Bernholt et al 2009). Based on the notion that the increasing urbanization accelerates the loss of biodiversity and displaces native species, a study in São Luís, North Brazil (Akinnifesi et al 2010) showed that the urban areas might serve as a repository of indigenous species, including those with risk of disappearance in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, muy poca investigación cuantitativa ha sido hecha con el intento de se comprender los jardines domésticos urbanos como sitios de conservación de la diversidad biológica La mayor parte de los estudios disponibles son meramente descriptivos, y métodos cuantitativos, incluyéndose herramientas estadísticas multivariantes que permitan desvelar estándares de la biodiversidad en los jardines domésticos urbanos raramente son usados (LORAM et al, 2008 (XIV ); MARCO et al, 2008;BERNHOLT et al, 2009).…”
Section: Funciones Ambientales De Los Jardines Urbanosunclassified